The Influence Of Social Media Marketing On Customer Brand Engagement In Forming Brand Loyalty At Kopi Janji Jiwa - Nyoman Tri Bintang Pertiwi; Oliandes Sondakh (PT. INOVASI TEKNOLOGI KOMPUTER, 2025)
The purpose of this study is to analyze the effect of Social Media Marketing which includes Entertainment, Customization, Interaction, Electronic Word of Mouth (EWOM), and Trendiness on Customer Brand Engagement as mediation which affects Brand Loyalty to Kopi Janji Jiwa in the three largest metropolitan city in Indonesia, which is Jakarta, Surabaya and Bandung.. This research model is conducted quantitatively using data taken by purposive sampling with questionnaires distributed online. A sample of 133 was obtained which met the requirements for analysis with PLS-SEM. The results showed that Entertainment and Interaction affect Customer Brand Engagement, where Entertainment is the most influential on Customer Brand Engagement. Then it was found that Customer Brand Engagement affects Brand Loyalty of Kopi Janji Jiwa. Based on the research results, managerial implications is to develop Instagram content and Instagram features in interacting with customers in building Customer Brand Engagement which encourages Brand Loyalty. The theoretical implications of this research are identifying Social Media Marketing element variables that can shape Customer Brand Engagement towards Brand Loyalty and developing research models and supporting previous research.